Analyzing the Determinants of Business Performance in Micro and Small Enterprises among Muslim Entrepreneurs in Aceh Province - Salam, Abdus; Imilda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to identify the factors influencing the business Performance of Micro, Small, and Medium Enterprises (MSEs) run by Muslim entrepreneurs in Aceh Province. MSEs play a vital role in the local economy; however, their business Performance is often hindered by various challenges, including limited resources and managerial issues. Several factors affecting the business Performance of SMEs in Aceh include entrepreneurial capacity, government support, access to Islamic finance, and the application of religious principles in business operations. This research employs a quantitative approach with a survey involving 120 Muslim entrepreneurs in Aceh as respondents. Data were collected through a questionnaire measuring factors related to management, financing, and the application of Islamic principles in business management. The factor analysis results identify three main variables that impact MSE Performance in Aceh: (1) business strategies, including planning, internal processes, and entrepreneurial orientation; (2) external support from the government; and (3) the implementation of Islamic principles in business practices. The first factor has the greatest impact on Performance, followed by government policy support and Islamic business practices. These findings can help stakeholders formulate policies that support SMEs in becoming more competitive and sustainable in the market while emphasizing the religious values that guide business management among Muslim entrepreneurs in Aceh.